2020
DOI: 10.3390/ijms21103580
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Long Non-Coding RNAs in Lung Diseases

Abstract: Within the non-coding genome landscape, long non-coding RNAs (lncRNAs) and their secretion within exosomes are a window that could further explain the regulation, the sustaining, and the spread of lung diseases. We present here a compilation of the current knowledge on lncRNAs commonly found in Chronic Obstructive Pulmonary Disease (COPD), asthma, Idiopathic Pulmonary Fibrosis (IPF), or lung cancers. We built interaction networks describing the mechanisms of action for COPD, asthma, and IPF, as well as private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 249 publications
(427 reference statements)
1
48
0
Order By: Relevance
“…12 13 MiRs have emerged as potent modulators of various cellular processes such as proliferation, migration, differentiation, inflammation and their utility as biomarkers of pulmonary fibrosis is being explored. [14][15][16][17][18] Indeed, Lui et al found an upregulation of miR-21-5p in…”
Section: Introductionmentioning
confidence: 99%
“…12 13 MiRs have emerged as potent modulators of various cellular processes such as proliferation, migration, differentiation, inflammation and their utility as biomarkers of pulmonary fibrosis is being explored. [14][15][16][17][18] Indeed, Lui et al found an upregulation of miR-21-5p in…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, evidences of involvement of exosomal lncRNA in lung pathologies including lung cancer, tuberculosis (TB), chronic obstructive pulmonary disease (COPD), asthma, and interstitial lung disease (ILD) are increasing [1,[11][12][13][14][15]. It has been demonstrated that the exosomal microRNAs (miRNA) and lncRNA profiles among patients with pulmonary pathologies are quite distinct than healthy individuals [12,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, TGF-β was found increased in IS of SSc patients without any difference between SSc-ILD and SSc-nonILD patients. In that context, we can hypothesize that the fibroblastic responsiveness under TGF-β stimulation could vary between patients suffering from SSc inducing a personal susceptibility to develop ILD partly induced by genetic, environmental and inflammatory factors [38][39][40]. Interestingly, we found a negative correlation between IS TGF-levels and Δ FEV-1%.…”
Section: Discussionmentioning
confidence: 65%